A case report of cervical spondylotic radiculopathy with superficies excess syndrome of cold pathogen of Taiyang treated by five-element cupping therapy (五行能量罐在项痹太阳伤寒表实证中的应用个案报道) - JIANG Jing (姜婧); WEI Yongchun (魏永春); MA Jianhua (马建华); WANG Yali (王亚丽); TANG Ling (唐玲) (Journal of International Translational Medicine Limited, 2021)
This paper summarized the nursing strategies for a patient with cervical spondylotic radiculopathy with superficies excess syndrome of cold pathogen of Taiyang treated by five-element cupping therapy. In addition to psychological nursing and dietary care, the five-element cupping therapy based on Traditional Chinese Medicine syndrome differentiation was carried out to relieve the symptoms of cervical spondylotic radiculopathy. (总结1例项痹太阳伤寒表实证患者受寒后采用五行能量罐的治疗护理经验。护理人员在心理、饮食等常规护理干预的基础上, 通过中医辨证理论指导, 取督脉、足太阳膀胱经、足少阳胆经之经络, 运用五行能量罐循经治疗, 以减轻患者背部发凉怕冷症状。)